Solving economic load dispatch problem using genetic algorithm method / Norliza Kamarulzaman - Kamarulzaman, Norliza (2009)
This thesis studies an approach to solve economic load dispatch problem on operation of power systems. The determination of power system operation of data is based on the generation output and coefficients involved. In this study, Genetic Algorithm method is used to overcome this problem. Data taken from the test system is analysed as the power system data generation. The objective of this paper is to find the generation scheduling such that the total operating cost can be minimized. Genetic Algorithm Toolbox functions in MATLAB program are utilized in solving the proposed method. The proposed method is tested on a system consisting power generating units. The results show that the proposed method provides the minimum cost was compared with recorded data of traditional method using table comparison. Thus, the comparison showed the minimum total operating cost of data generation was achieved.